Analisis Reaksi Pasar: Abnormal Return Dan Trading Volume Activity Sebelum Dan Setelah Pandemi Covid-19 Di Indonesia Pada Perusahaan Yang Terdaftar Di LQ45 Bursa Efek Indonesia - Yongki Adi Saputra; Liza Alvia; Usep Syaipudin; Ade Widyanti (Journal on Education, 2024)
Investing in capital market requires relevant information for decision-making and investment strategies. The capital market is sensitive to both economic and non-economic events. Market reactions to information are reflected through trading volume and changes in stock prices. News about COVID-19 and government policies restricting social activities have an impact on the capital market. PPKM (Enforcement of Restrictions on Community Activities) policies affect the stability of the capital market. The pandemic creates uncertainty, reflected in the decline of the IHSG (Indonesia Stock Exchange Composite Index) and changes in investor behavior. The purpose of this research is to compare Trading Volume Activity (TVA) and Abnormal Return (AR) in Indonesia before and after the COVID-19 pandemic. The aim is to identify statistically significant differences in Abnormal Return between the periods before and after announcement of PPKM, there is a significant increase in Trading Volume Activitys, indicating a more active market reaction to the PPKM events in Indonesia.